Nameplate, The Bombay Samachar Pvt. Ltd. - Ghosh, Ayan (2023)
Bombay Samachar is very popular among the Gujarati population living both in Bombay and Gujarat, and the diaspora. In its Gujarati publication, the newspaper is titled Mumbai Samachar. This dual use of names is an early example where Mumbai and Bombay were used interchangeably, long before Bombay was officially renamed Mumbai (1995).